Multiple Description Coding Using A New Bitplane-LVQ Scheme. - Syafalni, Infall; M. Salleh, M. F. (2010)

(untitled)
In this paper, a novel Bitplane-LVQ technique to compress subbands bitplane coefficients is proposed for multiple description coding (MDC) system.